1995
DOI: 10.1002/anie.199505851
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Structure of a Self‐Assembled Gelating Fiber

Abstract: Almost seventy years ago, chemist Dorothy Jordan noted that "gels are easier to recognize than to define"."] We will attempt a definition nonetheless : Gels are semi-rigid colloidal systems rich in liquid. Protoplasm ranks as the most widespread example of this peculiar state of matter. A gel is formed by a molecular network, often fibrous in nature, that entrains the dispersing medium within its capillary spaces. Most organic gelators are polymeric (for example, gelatin, ['] poIy(acry1ic acid) ,I3] and hyalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 13 publications
4
60
0
Order By: Relevance
“…Systematic characterizations of the gels with UV/Vis, FTIR, 1 HNMR, and X-ray diffraction (XRD) spectra were performed to identify the intermolecular interactions and the driving force for the formation of organogels. [45][46][47][48][49][50] Compared with TP-1,i n the dilute toluenes olution, the UV/Vis absorption peak of QP-1,a ssigned to the p-p*t ransition, shifted to longerw avelengths (ca. 317 nm for TP-1 and 324 nm for QP-1,F igure S4 in the Supporting Information) owing to the elongation of the conjugated core.…”
Section: Uv/vis Ftir 1 Hnmr and Xrd Spectramentioning
confidence: 99%
“…Systematic characterizations of the gels with UV/Vis, FTIR, 1 HNMR, and X-ray diffraction (XRD) spectra were performed to identify the intermolecular interactions and the driving force for the formation of organogels. [45][46][47][48][49][50] Compared with TP-1,i n the dilute toluenes olution, the UV/Vis absorption peak of QP-1,a ssigned to the p-p*t ransition, shifted to longerw avelengths (ca. 317 nm for TP-1 and 324 nm for QP-1,F igure S4 in the Supporting Information) owing to the elongation of the conjugated core.…”
Section: Uv/vis Ftir 1 Hnmr and Xrd Spectramentioning
confidence: 99%
“…Enhancement of the stability and robustness of these self-organized structures may rely on a combination of different intermolecular interactions. [10,11] Inspired by the early work of Fuhrhop et al and Ringsdorf and co-workers on the self-organization of bola-amphiphiles, [12,13] we have introduced rigid mesogenic groups or strong p-p-stacking moieties into bolaamphiphiles, resulting in significantly enhanced stability of the self-assembled structures. [14,15] In this Communication, we describe the design and synthesis of a new bola-amphiphile with two carboxylic acid end groups and a diketopyrrolopyrrole (DPP) chromophore in the central part.…”
mentioning
confidence: 99%
“…Recent investigations showed that only the pure enantiomer forms gels whereas the racemate crystallizes, and that both hydrogen bonding and π-stacking interactions are important for gelation [27]. In addition, D-glucose, D-galactose and D-mannose-benzylidene derivatives have recently been reported as potent organogelators [28], as well as a number of other compounds which gelate organic solvents via intermolecular hydrogen bonds [29,30,31,32,33,34]. …”
Section: Figure 4 Amide and Carbohydrate Containing Gelatorsmentioning
confidence: 99%